##### Ad

related to**K.C**

Sort by

- Relevance
- |Time

First off, note that ln(1) is an actual constant and simplifies to 0. The problem is now reduced to (VKC)/F=(1+E)*0-EX So now, you have a variable multiplied by X. To get rid of it, you want to divide both...

2 Answers · Science & Mathematics · 12/07/2009

Firstly, solving the original equation. x/3 = y + 2/3. Multiplying everything by 3 leaves x = 3y + 2. Now that we have an equation for x, we can solve the expression (x + 7)/3. Using the formula for x above, x + 7 = (3y + 2) + 7 = 3y + 9. Then, (x + 7)/3 = (3y + 9)/3 = y + 3...

5 Answers · Science & Mathematics · 24/06/2010

I am assuming that i,j,

**k**represent a 3 d system and therefore a and b are vectors a = {2, -4, -1};**c**= {3, 1, -2}; and a.**c**is the Dot Product then a.**c**= 42 Answers · Science & Mathematics · 11/11/2013

**C**=**k**/ (m(1 -**k**)) cross multiply Cm(1 -**k**) =**k**distribute LHS Cm - Cmk =**k**add Cmk to both sides Cm =**k**+ Cmk factor Cm =**k**(1 + Cm) divide both sides by (1 + Cm) Cm / (1 + Cm) =**k**...3 Answers · Science & Mathematics · 26/08/2008

Note that the characteristic of this equation is: y^2 + 1 = 0. This solves to yield y = ±i and the solutions would be: y = K*sin(t) + C*cos(t), for some constants K and C. I hope this helps!

4 Answers · Science & Mathematics · 31/03/2011

y=6-2sin1/2(x+45) distribute the 1/2 y=6-2sin[x/2-22.5)

1 Answers · Science & Mathematics · 15/07/2010

Suppose that you know that m = 2 and

**c**= 3. You need to examine the x- and y- asymptotes. There is no way that x could equal 0 in this equation because any number divided by 0 is undefined, so if you were to substitute 0 for x in the equation you would get y...3 Answers · Science & Mathematics · 24/08/2008

A) div F = (∂/∂x)(9yz) + (∂/∂y)(5xz) + (∂/∂z)(6xy) = 0. B) curl F = |..i.......j.......k...| |∂/∂x..∂/∂y..∂/∂z| = (x) i + (3y) j + (-4z) k. |9yz...5xz...6xy| C) Using part B, div(curl F) = (∂/∂x)(x) + (∂/∂y)(3y) + (∂/∂z)(-4z) = 0...

1 Answers · Science & Mathematics · 09/12/2013

Note that curl F = <x, -y, 0>. Moreover, let S be the surface inside C. So, ∫c F · dr = ∫∫s curl F · dS, by Stokes' Theorem = ∫∫ <x, -y, 0> · <-(-2x), -(2y), 1>...

1 Answers · Science & Mathematics · 09/05/2011

##### Ads

related to**K.C**